Bipartisan support for small businesses: statements by politicians and legislative measures in Italy between 1996 and 2018 - Mangani, Andrea (Piccola Impresa / Small Business, 2023)
Purpose. National and international institutions frequently define small and medium-sized enterprises (SMEs) as the backbone of national economies. Accordingly, both left-wing and right-wing politicians make frequent statements regarding the importance of SME policies for fostering economic growth and employment opportunities. This paper presents a quantitative study of the alleged bipartisan support for small business. Design/methodology/approach. The empirical analysis considers the statements in support of small business, as reported by major national newspapers, of leaders of Italian political parties on the left and right. In addition, the empirical analysis reviews the legislative measures adopted by centre-left and centre-right national governments for SMEs between 1996 and 2018. Findings. The results show that the leaders of right-wing parties were more active, in the period under review, in expressing their support to small businesses, while centre-left governments adopted more legislative measures and allocated more funds in favour of SMEs. Practical and Social implications. These results provide an empirical background for assessing the position and credibility of the political and social actors that shape the discourse on SMEs in the public arena. Originality of the study. This paper is the first attempt to quantify the widespread and debated political support to small business.